EDUCATIONAL PSYCHOLOGY THINKING ACCORDING TO SHAYKH ABDULLAH FAHIM - KHAIRUL NIZAM BIN ZAINAL BADRI (Universitas Andi Djemma, 2021)
Educational psychology has undergone a change in the mid-20th century from using a traditional approach to an approach that looks at the intellectual, emotional and social development of students. In the context of education in Malaysia, the traditional approach refers to the practice of teaching and learning carried out in study huts. With such an approach, it is quite difficult to know the potential development of a student. The situation changed when the madrasah system was first introduced. In the madrasah system, studies are conducted according to classes and the syllabus is implemented according to the levels that have been set. This study seeks to examine the thinking of Shaykh Abdullah Fahim (1869 - 1961) an educator who was educated in the traditional stream, but engaged in the task of educating in the madrasah stream from the point of view of educational psychology. Another thing to know is how does he develop awareness and provide insight to students. This qualitative study found that Shaykh Abdullah Fahim is an educator who is wise in adapting the educational situation to the environment. By using a positive psychological approach, he develops mental strength, builds confidence and increases motivation in his students.